2021
DOI: 10.1002/adma.202007398
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐Independent Terahertz Anomalous Hall Effect in DyCo5, Co32Fe68, and Gd27Fe73 Thin Films from DC to 40 THz

Abstract: The anomalous Hall effect (AHE) is a fundamental spintronic charge‐to‐charge‐current conversion phenomenon and closely related to spin‐to‐charge‐current conversion by the spin Hall effect. Future high‐speed spintronic devices will crucially rely on such conversion phenomena at terahertz (THz) frequencies. Here, it is revealed that the AHE remains operative from DC up to 40 THz with a flat frequency response in thin films of three technologically relevant magnetic materials: DyCo5, Co32Fe68, and Gd27Fe73. The f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 78 publications
(139 reference statements)
0
13
0
Order By: Relevance
“…The good agreement of GHz and THz S2C efficiency in both thickness limits is consistent with previous studies that compared THz and low-frequency regimes of spin-orbit-couplingbased effects. 32,46,47 As y 0 ( y 1 in most cases, the IrMn layer behaves like a simple spin-current attenuator, and we can justify the mono-exponential approximation in Eq. ( 2).…”
mentioning
confidence: 77%
“…The good agreement of GHz and THz S2C efficiency in both thickness limits is consistent with previous studies that compared THz and low-frequency regimes of spin-orbit-couplingbased effects. 32,46,47 As y 0 ( y 1 in most cases, the IrMn layer behaves like a simple spin-current attenuator, and we can justify the mono-exponential approximation in Eq. ( 2).…”
mentioning
confidence: 77%
“…This charge current, 𝒋 𝒄 is given by 𝒋 𝒄 = 𝛾𝒋 𝒔 × 𝑴/|𝑴| 15 where 𝑴/|𝑴| denotes the magnetization unit vector of the FM layer and 𝛾 signifies the spin Hall angle of the HM layer. Recent studies have highlighted the potential of the linear relation between the 𝒋 𝒄 and 𝒋 𝒔 where the measure of 𝒋 𝒄 relates to the spin ordering in the system [17][18][19] . Empirically, the terahertz pulse amplitude follows the magnetization behavior of the FM 20,21 , however, the underlying microscopic processes are largely unexplored and require a rigorous investigation to establish the physical interpretations of the terahertz pulse amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…The conduction electrons involved in the super-diffusive transport model are located close to the Fermi level, making them equivalent to the conduction electrons in the diffusive transport model. Seifert et al 29 demonstrated that the anomalous Hall conductivity and anomalous Hall angle are frequency-independent up to 40 THz, and therefore consistent with the DC anomalous Hall conductivity within an error bar of 2%.
Figure 5 ( a ) Transmission ( T ), reflectance ( R ) and absorption ( A ) vs. .
…”
Section: Resultsmentioning
confidence: 65%